The ecological crisis and the logic of capital - Chen, Xueming, 1947- (Studies in Moral Philosophy, 2017)
The worsening environmental crisis has become a serious threat to mankind. The search for a solution to this crisis must begin by understanding its causes. Taking an eco-socialist perspective, The Ecological Crisis and the Logic of Capital explores the logic of capitalism as a fundamental cause of today's environmental crisis, in particular the thirst for profit and the capitalist mode of production. By demonstrating the inherent antagonism between capital and ecology, this book argues that proposals to resolve the crisis within the capitalist system are utopian, that proposed remedies relying on scientific progress, alternative energies, low-carbon technologies or the introduction of ecological ethics and new attitudes toward Nature into market mechanisms are doomed to failure without a radical overhaul of the principles that govern capitalism.